Assessment of domestic trade performance in developing economies: Integrated metrics, factor prioritization and strategic implications - Raimbekov, Zhanarys Sabirovich; Syzdykbayeva, Bakyt Uzakbayevna; Bauer, Maira Shakibaevna; Rauandina, Guldaray Kalkenovna (Asian Economic and Financial Review, 2025)
Domestic trade constitutes a critical driver of sustainable economic growth in emerging markets. However, assessing its efficiency remains challenging due to fragmented indicators and the absence of a unified methodology. This study aims to develop a comprehensive metric for evaluating the performance of the trade sector and identifying strategic priorities for its development. Using data from the Bureau of National Statistics of the Republic of Kazakhstan for the period 2001–2023, the analysis employs factor and regression analysis methods, complemented by expert evaluations to weight priority factors and enhance the precision of the aggregated indicator aligned with strategic development objectives. The study identifies four key groups of efficiency determinants socio-economic, production, infrastructure, and price-behavioral factors with purchasing power, employment, and the condition of trade infrastructure exerting the most significant influence. Production and infrastructure factors demonstrate a moderate impact, while price gross value-added variables gain importance under inflationary pressures. The proposed methodology offers a reliable diagnostic tool for monitoring sectoral sustainability and supports the development of targeted economic measures to enhance trade efficiency. Although the findings, based on the context of Kazakhstan, may require adaptation for broader application, the methodology remains pertinent for other emerging economies, considering differences in data availability and institutional maturity. Practical implications include providing policymakers and stakeholders with actionable insights to stimulate domestic production, improve logistics and institutional infrastructure, and strengthen strategic planning processes. This study presents a scalable framework for assessing trade efficiency and its impact on supply chain resilience in emerging markets.